A review on sensing-based strategies of interior lighting control system and their performance in commercial buildings - Khairul Rijal Wagiman; Mohd Noor Abdullah; Mohammad Yusri Hassan; Nur Hanis Mohammad Radzi (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Artificial lighting consumed significant amount of electrical energy in commercial buildings. Therefore, intelligent control strategies are widely implemented to reduce the lighting energy consumption. This paper presents comprehensive review of the current sensing-based strategies (i.e. occupancy, daylight and mixed), sensors placement methods (i.e. occupancy and light) and factors affecting the performance of the lighting control strategies. Based on literature survey, the sensors placement methods can be categorized into three approaches: fixed, mathematical equation and optimization. The state-of-the-art of these approaches are discusses in details. It found that, the optimization-based approach capable to find the optimal sensor placement (numbers and positions) effectively. Moreover, the mixed strategy can be produced the highest energy savings up to 95% compared with other strategies. The occupancy pattern and building characteristics are the main factors to contribute higher energy savings of sensing-based strategies in commercial buildings.